Structural Performance Of A Lightweight Composite Slab System - Yardim, Yavuz (2008)

(untitled)
Floor structure occupies the biggest dead load and volume in most of the residential buildings. Composite structure is the most proper concept to obtain lighter, cheaper and easy to construct floor system by optimally utilizing available materials. However, composite floor system efficiency under ultimate load remains a major concern. Longitudinal shear failure is the most common type of failure in composite floor slab. The existing shear links systems between cast in situ and precast layers are found very conservative due to absence of adequate investigation. Further investigations of connection systems between the precast composite units are sought. Therefore, Composite Ferrocement Masonry Slab (CFMS) is introduced as a new composite floor system in this study. Inverted two-way ribs precast ferrocement thin panel is used at tension part of the composite slab system and act as permanent formwork. Masonry element such as brick and autoclaved aerated concrete with concrete mortar are used as toping of the composite floor system to achieve lighter structure.Analytical study has been carried out to investigate the efficiency of Composite Ferrocement Masonry Slab as a composite floor system. A series of pilot tests have been conducted until ultimate load to ascertain structural characteristic of both precast and full slab system. The study proposes a new system to transfer the horizontal shear between the interfaces of the precast and cast in-situ layers of concrete slab as a substitute of shear links. The proposed system implements an interlocking concept and does not require any shear reinforcement. Experimental work carried out by pure shear loading (push off test) and flexural loading to study the effectiveness of the interlocking mechanism in transferring the stresses developed due to the applied load. Flexural test was carried out on full size specimens using different masonry elements to explore structural capacity. Finally, connection tests were carried out for slab to slab and slab-beam-slab connection for the composite precast slab system. The results in terms of strain distribution, load-deflection and failure loads indicate that the response of the composite slab to the flexural loading is satisfactory and can be used as a floor slab in residential buildings. The predicted ultimate load using BS8110 was found to be compatible with the experimental results. Ductile load deflection curves were drawn for the composite slab implied maximum deflection varied between 31 to 35 mm for 3 m span. The interlocking mechanism in the proposed composite slab system implied that 20 mm and above interlocking depth is enough to support maximum possible horizontal shear load on the slab structure. The composite slab system with interlocking mechanism acts as a full composite structure until ultimate load. The flexural capacity of this floor slab system is adequate to carry ultimate load 6.5 kN/m2 for brick masonry composite and 4.5 kN/m2 for (Autoclaved Aerated Concrete) AAC masonry composite. The composite slab is achieved using brick and AAC masonry 18% and 22 to 34 % lighter compare to RC slab respectively. The connection tests ascertain connectivity of the composite slab-beamslab system is well enough to carry residential loads. As a result the proposed composite slab systems may be used as composite precast slab for residential buildings.